IMPLEMENTATION OF THE STUNTING PREVENTION PROGRAM IN SEPANDE VILLAGE - Dwicaksono, Algarma Satriyo; Usrotin Choiriyah, Ilmi (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the implementation of the Stunting Prevention Program in Sepande Village, Candi District, Sidoarjo Regency, focusing on four indicators of George Edward III's implementation theory, namely communication, resources, disposition, and bureaucratic structure. Method: This study uses a qualitative descriptive approach with data collection through in-depth interviews with key informants (village officials, health workers, and posyandu cadres), field observations, and document reviews. Result: The results of the study show that the implementation of the program has been quite effective in terms of communication and resource availability, with clear information channels from the District Health Office to the village level and adequate support in the form of health equipment and supplementary food, while the disposition of the implementers can be seen from their strong commitment and proactive efforts to approach families with stunted toddlers, and the bureaucratic structure has been well organized through a clear division of tasks based on the Village Head's Decree, although there are still overlapping tasks and a lack of detail in the SOP, especially in home visits and case referrals. Novelty: The novelty of this study lies in its focus on the internal coordination mechanisms of the village bureaucracy, which has been understudied in previous research that has emphasized program outcomes, with recommendations including strengthening horizontal coordination across sectors, detailing SOPs, and improving the monitoring system to ensure more sustainable stunting reduction at the village level.